Prospects for repurposing CNS drugs for cancer treatment - Mohamed Abdelaleem; Hossam Ezzat; Muhammed Osama; Adel Megahed; Waleed Alaa; Ahmed Gaber; Ayman Shafei; Alaa Refaat (Frontiers Media S.A., 2019)
Drug repurposing is the idea of using an already approved drug for another disease or disorder away from its initial use. This new approach ensures the reduction in high cost required for developing a new drug in addition to the time consumed, especially in the tumor disorders that show an unceasing rising rate with an unmet success rate of new anticancer drugs. In our review, we will review the anti-cancer effect of some CNS drugs, including both therapeutic and preventive, by searching the literature for preclinical or clinical evidence for anticancer potential of central nervous system drugs over the last 8 years period (2010-2018) and including only evidence from Q1 journals as indicated by Scimago website (www.scimagojr.com). We concluded that Some Central Nervous system drugs show a great potential as anti-cancer in vitro, in vivo and clinical trials through different mechanisms and pathways in different types of cancer that reveal a promising evidence for the repurposing of CNS drugs for new indications.